Corporate reputation and responsibility tracking, and disaster recovery - Macleod, Sandra; Middlemiss, Nigel (Henry Stewart Talks, 2008)
The importance of reputation, Frameworks and tools for reputation tracking, Evaluating reputation in the media, in CGM (Citizen-Generated Media) and among stakeholders, Tracking and reporting on corporate responsibility, Disaster recovery, Creating an integrated and holistic perspective, The way forward